INTERNET DAN PERILAKU CYBERLOAFING PADA KARYAWAN - Mirza Mirza; Thaybatan AR; Harri Santoso (Psikoislamedia : Jurnal Psikologi, 2019)
The existence of internet facilities has brought good changes in various aspects with the number of users for Indonesia reaching 132.7 million people, where internet users are dominated by Workers / Employees. The internet provides opportunities for employees to more easily improve performance, interact and create inspiration and creativity. But the internet can also have negative effects such as the occurrence of work procrastination behavior on employees that can interfere with productivity caused by the temptation caused by the internet, as a result of distraction at work through the activity of browsing various sites on the internet, who then reducing cognitive resources to work on their obligations. This study was the beginning or preliminary method using descriptive methods that examine cyberloafing of workers, as a new form of problems in the work environment so that they need to be watched and anticipated in order to increase employee and organizational productivity.